Penyuluhan Tentang Cara Mengatasi Morning Sickness Dan Pengukuran Lingkar Lengan Atas Pada Ibu Hamil Di Praktek Mandiri Bidan Jaba - Sagitarini, Putu Noviana; Wisnawa, I Nyoman Dharma (UNIVERSITAS NGUDI WALUYO, 2022)
Pregnant women are a group that is most vulnerable to nutritional problems because it can affect the growth and development of the fetus they contain. One of the nutritional problems of pregnant women in Indonesia is chronic energy deficiency. LILA measurement is an indicator to determine whether pregnant women are at risk of experiencing chronic energy deficiency or not. Another problem that also affects the nutrition of pregnant women that often appears in the first trimester of pregnancy is morning sickness. To reduce the incidence of morning sickness in pregnant women, namely providing health education about self-management for primigravida pregnant women. In self-management, pregnant women can change healthy living behavior or new habits according to their conditions. The purpose of this activity is to increase the knowledge of pregnant women about how to deal with morning sickness and the measurement of LILA in pregnant women to determine their nutritional status. The hope of this activity is that participants in this activity will experience an increase in knowledge related to how to overcome morning sickness and know the nutritional status of pregnant women so that they can carry out healthy lifestyle behaviors so that the pregnancy process runs smoothly.ABSTRAKIbu hamil merupakan suatu kelompok yang paling rawan terhadap masalah gizi karena dapat mempengaruhi tumbuh kembang janin yang dikandung. Salah satu masalah gizi ibu hamil di Indonesia yaitu kekurangan energi kronis. Pengukuran LILA adalah indikator untuk mengetahui apakah ibu hamil beresiko mengalami kurang energi kronis atau tidak. Masalah lain yang juga mempengaruhi gizi ibu hamil yang sering muncul pada kehamilan trimester pertama yaitu morning sickness. Untuk mengurangi kejadian morning sickness pada ibu hamil yaitu memberikan health education tentang self management pada ibu hamil primigravida. Dalam self management ibu hamil dapat mengubah perilaku hidup sehat atau kebiasan yang baru sesuai dengan kondisinya. Tujuan kegiatan ini meningkatkan pengetahuan ibu hamil tentang cara mengatasi morning sickness dan pengukuran LILA pada ibu hamil untuk mengetahui status gizinya. Harapan dari kegiatan ini adalah peserta dalam kegiatan ini mengalami peningkatan pengetahuan terkait cara mengatasi morning sickness dan mengetahui status gizi ibu hamil sehingga bisa melakukan perilaku hidup sehat agar proses kehamilan berjalan lancar.